Essays On Corruption And Economic Development - Freille, Sebastian (2007)
This thesis addresses two central questions in the field of corruption: the relationship between corruption and some of its main determinants and the effect that these relationships have on economic development. The research presented in this thesis extends the literature on corruption in several directions.